2014
DOI: 10.2337/dc14-1237
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Canagliflozin, an Inhibitor of Sodium–Glucose Cotransporter 2, When Used in Conjunction With Insulin Therapy in Patients With Type 2 Diabetes

Abstract: OBJECTIVEThere are limited data about the effects of sodium-glucose cotransporter 2 inhibitors when used with insulin. We report the efficacy and safety of canagliflozin in patients with type 2 diabetes using insulin. RESEARCH DESIGN AND METHODSThe CANagliflozin CardioVascular Assessment Study is a double-blind, placebocontrolled study that randomized participants to placebo, canagliflozin 100 mg, or canagliflozin 300 mg once daily, added to a range of therapies. The primary end point of this substudy was the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

26
231
2
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 213 publications
(263 citation statements)
references
References 31 publications
26
231
2
4
Order By: Relevance
“…These studies were published between 2008 and 2015 from 14 countries including the United States of America (8 studies), United Kingdom (8 studies), Japan (5 studies), Germany (5 studies), Canada (4 studies), Italy (3 studies), Sweden (3 studies), and 1 study from each of Mexico, Austria, Netherlands, Finland, Poland, China, and Australia. The number of participants included in studies ranged from 2720 to 2072 47. All of these studies were randomized clinical trials with durations of 4 weeks (1 trial), 12 weeks (12 trials), 24 weeks (11 trials), 26 weeks (4 trials), 48 weeks (2 trials), 52 weeks (7 trials), 102 weeks (2 trials), 104 weeks (2 trials), and 208 weeks (1 trial).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies were published between 2008 and 2015 from 14 countries including the United States of America (8 studies), United Kingdom (8 studies), Japan (5 studies), Germany (5 studies), Canada (4 studies), Italy (3 studies), Sweden (3 studies), and 1 study from each of Mexico, Austria, Netherlands, Finland, Poland, China, and Australia. The number of participants included in studies ranged from 2720 to 2072 47. All of these studies were randomized clinical trials with durations of 4 weeks (1 trial), 12 weeks (12 trials), 24 weeks (11 trials), 26 weeks (4 trials), 48 weeks (2 trials), 52 weeks (7 trials), 102 weeks (2 trials), 104 weeks (2 trials), and 208 weeks (1 trial).…”
Section: Resultsmentioning
confidence: 99%
“…Data were sorted by first author, year of publication, country of the study, design, age range of the participants, total sample size, SGLT2 inhibitor, comparator, number of patients, dosage, and follow‐up duration (Table 1). 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55 …”
Section: Methodsmentioning
confidence: 99%
“…While the insulin‐independent mechanism of canagliflozin leads to a low inherent risk of hypoglycaemia, the mild osmotic diuresis it causes may be associated with an increased risk of volume–depletion events, including dehydration. Across Phase 3 studies in a broad range of patients, canagliflozin provided reductions in HbA1c, body weight, and systolic blood pressure (BP) and was generally well tolerated, with a low risk of hypoglycaemia when not used in conjunction with insulin or sulphonylureas 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22. An analysis of T2DM patients living in hot climates found that canagliflozin treatment was generally well tolerated, with a low incidence of volume depletion–related AEs 23…”
Section: Introductionmentioning
confidence: 99%
“…Canagliflozin (CANA) is an SGLT2 inhibitor developed for the treatment of adults with type 2 diabetes (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). CANA lowers the renal threshold for glucose, thereby increasing urinary glucose excretion (UGE); increased UGE results in insulinindependent glucose-lowering effects, as well as a mild osmotic diuresis and net caloric loss that can lead to weight loss and blood pressure (BP) reductions (24,25).…”
mentioning
confidence: 99%